Bourgin-Yang-type theorem for a-compact perturbations of closed operators. Part I. The case of index theories with dimension property - Sergey A. Antonyan; Zalman I. Balanov; Boris D. Gel'man (Abstract and Applied Analysis)
A variant of the Bourgin-Yang theorem for a-compact perturbations of a closed linear operator (in general, unbounded and having an infinite-dimensional kernel) is proved. An application to integrodifferential equations is discussed.